2001
DOI: 10.1007/s100480100116
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of p53 mutation and expression in pleomorphic xanthoastrocytoma

Abstract: Pleomorphic xanthoastrocytoma (PXA) is a rare, superficially situated tumor that most frequently occurs in the temporal lobe of young adults and is often associated with seizures. It generally has a relatively favorable prognosis. Prior studies have shown that TP53 mutations may occur in up to 25% of PXAs, suggesting that PXA may have an etiology similar to diffuse astrocytoma rather than pilocytic astrocytoma. In the present study, we performed immunostaining for p53 protein and examined the mutation status o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 11 publications
1
31
0
2
Order By: Relevance
“…Comparative genomic hybridization (CGH) analysis of three PXAs detected gain on chromosome 7 and loss on 8p as recurrent imbalances (Yin et al, 2002). Molecular genetic studies revealed that mutations in the TP53 tumor-suppressor gene are restricted to a small fraction of cases (Paulus et al, 1996;Giannini et al, 2001;Kaulich et al, 2002). Thus, to date no specific genetic aberration has been linked to PXAs.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative genomic hybridization (CGH) analysis of three PXAs detected gain on chromosome 7 and loss on 8p as recurrent imbalances (Yin et al, 2002). Molecular genetic studies revealed that mutations in the TP53 tumor-suppressor gene are restricted to a small fraction of cases (Paulus et al, 1996;Giannini et al, 2001;Kaulich et al, 2002). Thus, to date no specific genetic aberration has been linked to PXAs.…”
Section: Introductionmentioning
confidence: 99%
“…Immunopositivity of neuronal markers such as synaptophysin, Class III beta tubulin, neurofilament protein had been reported [11] [12]. As an astrocytic marker, p53 is negative or focally positive [18]. Vu et al observed GFAP positivity in 22 cases, S-100 positivity in 11 cases, Neurofilament positivity in 7 of 13 tested cases, synaptophysin in 5 of 12 tested cases [17].…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation and determination of the discriminating role of immunohistochemical stains is difficult regarding the existence of cases in the literature reported as immunonegative for neuronal and astrocytic markers. Giannini et al specifically suggested that p53 was strongly positive in GBM's and therefore this feature could be useful in differential diagnosis of APXA [18].…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, Giannini et al [44]published their analysis of p53 mutation and expression in 55 PXA cases. Of these, only 35 were typical PXAs, whereas the remaining 20 (36%) showed varying degrees of anaplastic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, only 35 were typical PXAs, whereas the remaining 20 (36%) showed varying degrees of anaplastic changes. Giannini et al [44]concluded that p53 mutation (2%) was an uncommon genetic event in PXA formation and probably not involved in tumor progression.…”
Section: Discussionmentioning
confidence: 99%